Molecular Detection and Genotyping of Theileria spp. in Deer (Cervidae) in Korea - Chang Uk Chung; Haeseung Lee; Min-Goo Seo; Seung-Hun Lee; Kyoo-Tae Kim; Kaifa Nazim; Jung-Sun Song; Dong Hwa Bae; Man Hee Rhee; Oh-Deog Kwon; Dongmi Kwak (Microorganisms, 2023)
Major clinical symptoms of Theileria infection include fever, anemia, anorexia, jaundice, and decreased milk production. Although several studies have been conducted on tick-borne pathogens, including Theileria in Korea, only a few have focused on Theileria infection in deer, including the Korean water deer. Blood samples from 160 deer were collected and subjected to DNA extraction and polymerase chain reaction (PCR). Next, PCR-positive samples were sequenced and analyzed by constructing a phylogenetic tree. The results showed that the overall infection rate of Theileria was 8.1% (13/160). Infection rates of 100% were observed in the northern and southern regions. However, the study’s limitation was its small sample size, wherein five and one samples were analyzed from the northern and southern regions, respectively. The central region exhibited the lowest infection rate of 2.9% (4/140). Infection rates also differed based on seasons, with the highest (18.4%, 9/49) being observed in spring, followed by that in summer (8.9%, 4/45). However, no infection was observed during autumn and winter. A phylogenetic analysis indicated that the PCR-positive samples contained Theileria luwenshuni, which usually infects small ruminants, such as goats and sheep.